A bZIP transcription factor GhVIP1 increased drought tolerance in upland cotton - Pei Zhao; Yuewei Xu; Wei Chen; Xiaohui Sang; Yunlei Zhao; Hongmei Wang (Journal of Cotton Research, 2023)
Abstract Background Cotton is extremely affected by severe natural stresses. Drought is one of the most serious abiotic stress that adversely influences cotton growth, productivity, and fiber quality. Previous studies indicate that basic leucine-zipper (bZIP) transcription factors are involved in the response of plants to various stresses. However, the molecular function and regulatory mechanism of GhVIP1 in response to drought stress are still unknown. Results In this research, GhVIP1 was cloned from a drought-tolerant variety. Expression of GhVIP1 was up-regulated in response to multiple abiotic stresses, especially under drought stress. And GhVIP1 was highly expressed in the root, stem, and 10 days post-anthesis ovule. Inhibiting the expression of GhVIP1 in cotton using the virus-induced gene silencing method resulted in higher electrical conductivity in leaves, but lower water content under drought stress compared with the WT plant. Overexpression of GhVIP1 in Arabidopsis enhanced plant drought tolerance through increasing the seed germination rate and improving the development of root. The exogenous expression of GhVIP1 up-regulated the transcription of genes associated with drought response and proline biosynthesis during drought stress in Arabidopsis. Conclusion In summary, these results indicated that GhVIP1 played a positive role in plants' response to drought stress. The use of GhVIP1 via modern biotechnology might facilitate the improvement of drought tolerance in cotton cultivars.